The meaning of resilience for child development from a biopsychosocial perspective - Kungl, Melanie; Gabler, Sandra; Spangler, Gottfried (Psychologie in Erziehung und Unterricht, 2023)
Since the beginning of resilience research, the construct of resilience has undergone major changes. The current article gives an overview of pioneering studies and their findings embedding them into different theoretical approaches. It further describes related models (e. g., risk and protection model) and discusses potential effects of protective factors. However, from today's perspective resilience neither solely describes well-defined protective factors nor stable inherent personality traits. Rather is it understood as a dynamic construct, while also taking into account biological mechanisms. Importantly, on different levels it comes to light that the attachment figure's behaviour plays a crucial role for resilience, e. g. regarding relevant epigenetic changes, buffering effects in light of adversity or the acquisition of resilience promoting competencies. Finally, the current article closes with addressing this issue by discussing resilience from an attachment theory perspective emphasizing that people outside the biological family can function as significant attachment figures (foster families, teachers) and therefore should be target of prevention and intervention as well.
CRIS-Team WoS Importer:2023-03-03